The history of RNAi and microRNA discovery - Tan, GC (Penerbit UKM, 2014)
MicroRNAs belong to one of the classes of non-coding RNAs. Non-coding RNAs are functional RNAs that do not translate into protein. They comprise: transfer RNA (tRNA); ribosomal RNA (rRNA); small nucleolar RNA (snoRNA); microRNA (miRNA); small interfering RNA (siRNAs); small nuclear RNA (snRNA); piwi-interacting RNA (piRNA), and long ncRNA. To date, there are approximately 1881 pre-miRNAs and 2588 mature human miRNAs have been identified (miRBase, June 2014). MicroRNAs are about 19-25 nucleotides in length and are now known to have important post-transcriptional roles in almost every cellular process in eukaryotes. These processes include the regulation of developmental timing and signalling pathways, apoptosis, metabolism, myogenesis and cardiogenesis, brain development, and human pathologies like viral diseases, genetic disorders and cancer (Shi et al. 2008).